PENGARUH KOMPETENSI PEDAGOGIK GURU DAN STRES KERJA TERHADAP KINERJA GURU DI SD NEGERI 104217 SIDOMULYO, SD NEGERI 104218 SIDOMULYO DAN SD NEGERI 101807 CANDIREJO DI KECAMATAN SIBIRU-BIRU - Sinaga, Esther Primavera; Lubis, Andrew Satria; Yulinda, Yulinda; Anna, Lucy (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine and analyze pedagogikal competence and work stress on teacher performance at SDN 104217 Sidomulyo, SDN 104218 Sidomulyo and SDN 101807 Candirejo in Sibiru-biru District. This research is associative research, namely: research that looks for the relationship between one variabel and the loan variabel. The types of data used are: secondary data and primary data collected by interviews, distributing questionnaires and documentation studies. The hypothesis in this research is that pedagogikal competence and work stress influence teacher performance at SDN 104217 Sidomulyo, SDN 104218 Sidomulyo and SDN 101807 Candirejo in Sibiru-biru District. The data analysis method used is the multiple linear method. The sample in this study was 50 respondents. The sampling technique used in this research was the total sampling method. The results of the simultaneous significant test (F-test) were Fcount (26.988) FTabel (3.20) and the significance value (0.000) ɑ (0.05). The results of this research show that simultaneously pedagogikal competence and work stress have a positive and significant effect on teacher performance at SDN 104217 Sidomulyo, SDN 104218 Sidomulyo and SDN 101807 Candirejo in Sibiru-biru District.